Pengaruh Sistem Bagi Hasil dan Tingkat Suku Bunga terhadap Keputusan Pengambilan Kredit oleh Usaha Mikro Kecil dan Menengah (Studi pada BMT Insan Madani Magetan) - Wijianto Wijianto; Sri Hartono (Departement of Mathematics Education, 2023)
This study aims to determine the effect of the profit-sharing system and interest rates on the decisions of SME customers in taking credit as a business to develop their business, this research was conducted on BMT Insan Madani Magetan customers in financing Micro, Small and Medium Enterprises. The testing technique used is multiple linear regression analysis, hypothesis testing, validity test, simultaneous test and the results show that the profit sharing system has no effect on credit making decisions by MSMEs. The interest rate variable has a significant effect on credit making decisions by MSMEs. With Variable X1 Profit Sharing System, Variable 2 Interest Rate and Variable Y is Credit Decision.